Adductor Canal Block Can Result in Motor Block of the Quadriceps Muscle. Issue 2 (1st March 2014) - Chen, Junping; Lesser, Jonathan B.; Hadzic, Admir; Reiss, Wojciech; Resta-Flarer, Francesco
Abstract : Objective: The block of nerves in the adductor canal is considered to cause a sensory block without a motor component. In this report, we describe a case of significant quadriceps muscle weakness after an adductor canal block (ACB). Case Report: A 65-year-old female patient for ambulatory knee surgery was given an ACB for postoperative pain management. The block was performed under ultrasound guidance at the midthigh level using the transsartorial approach. Twenty milliliters of 0.5% ropivacaine was deposited adjacent to the anterior and posterior areas of the femoral artery. On discharge from the hospital, the patient realized that her thigh muscles were weak and she was unable to extend her leg at the knee. A neuromuscular examination indicated that the patient had no strength in her quadriceps muscle, along with sensory deficit in the medial-anterior lower leg and area in front of knee up to the midthigh. The weakness lasted 20 hours, and the sensory block lasted 48 hours before complete recovery. The optimal level and amount of local anesthetic for adductor canal block are currently not well defined. Proximal spread of local anesthetic and anatomical variation may explain our observation. Conclusions: Several studies have reported that ACB involves no motor blockade. However, our case report illustrates that the ACB can result in clinically significant quadriceps muscle paralysis. This report suggests that patients should be monitored vigilantly for this occurrence to decrease the risk of falls.